التفسير المقاصدي للحدود في القرآن الكريم: حد الرجم أنموذجا: دراسة في تفسير التحرير والتنوير لابن عاشور: The Purposive Exegesis of the Punishments in Qur’an: Hadd of Stoning as a Model: A Study of Tafsir al-Tahrir wa al-Tanwir by Ibn e Ashoor) (Al Basirah, 2025)
The Objective-based approach to Qur'anic interpretation is considered one of the most prominent methodologies adopted by many exegetes in their works. This approach is centered on uncovering the general and specific, as well as the universal and partial objectives revealed in the Holy Qur'an, with the aim of establishing a Qur'anic system that achieves benefits, prevents harm, and reforms both the individual and society, considering the teachings of Islamic law. Various books and theses have been written about the objective based approach to Quranic interpretation, for example: "Maqasid al-Shari'ah in Punishments, Purposive Exegesis of Qur'anic Surahs in the Shadow of the Qur'an and Purposive Exegesis of the Qur'an: Foundations and Applications, however this paper discusses Tafsir al-Tahrir wa al-Tanwir by Ibn e Ashoor. Muhammad al-Ṭāhir ibn ʿĀshūr (1879–1973) was one of the academics who gave this method extraordinary attention. His famous exegesis, Al-Taḥrīr wa al-Tanwīr, which has become a cornerstone in the field for those who followed him, amply demonstrates his dedication to this methodology. This article aims to introduce the Maqāṣid-based interpretation of the Hadd of stoning for adulterers, as well as the profound wisdom behind its legislation within this interpretive framework. The research problem focuses on how Ibn ʿĀshūr used the Maqāṣidic method to explain the punishment of stoning for married adulterers, what important reasons and wisdom support this law, and how this method can address the doubts and objections raised about this punishment in today's discussions. This article adopts an analytical and deductive methodology by tracing Ibn ʿĀshūr’s expressions in his exegesis on the Hadd of stoning from a Maqāṣidic perspective, analyzing these expressions to highlight the underlying legal wisdoms, and discussing them considering methodological research principles. This study found that Ibn ʿĀshūr’s view on the Hadd of stoning, using the Maqāṣidic approach, strikes a balance between protecting the five key goals of Islamic law.
Keywords: Objective Exegesis; Ibn ʿĀshūr; Al-Taḥrīr wa al-Tanwīr; Punishments; Stoning in adultery